Deciphering Descriptive Text Challenges: Seventh-Grade Students' Writing Difficulties: Membongkar Tantangan Menulis Teks Deskriptif: Kesulitan dan Penyebab pada Siswa Kelas Tujuh - Titan Nur Maulidiyah; Vidya Mandarani (Academia Open, 2023)
This qualitative descriptive research explores the challenges faced by seventh-grade students in writing descriptive text and identifies their underlying causes. The study, conducted at SMP PGRI 16 Sidoarjo, employed students' writing exercises and interviews with an English teacher and first-grade students as data instruments. The analysis revealed three key areas of difficulty: generic structure, grammar (including the use of nouns, pronouns, conjunctions, prepositions, and simple present tense), and spelling. The identified causes encompassed inadequate English proficiency, insufficient knowledge of descriptive text material, disinterest in learning English, as well as internal and external factors such as family background and students' skills and capabilities. The findings shed light on the specific areas of difficulty and their root causes, providing valuable insights for educators and curriculum developers aiming to enhance students' proficiency in writing descriptive text. Highlights: Students' difficulties in writing descriptive text: The study identifies challenges in the generic structure, grammar, and spelling faced by seventh-grade students. Causes of difficulties: The research uncovers factors such as English proficiency, knowledge gaps in descriptive text material, lack of interest in learning English, and internal/external influences. Implications for educators: The findings offer insights to enhance instructional approaches and curriculum development for improving students' proficiency in descriptive text writing. Keywords: descriptive text, seventh-grade students, difficulties, causes, qualitative research.